Longer Working Hours and Maternal Mental Health: A Comparison of Single vs. Partnered Mothers - Julija Simpson; John Wildman; Clare Bambra; Heather Brown (Institute of Labor Economics (IZA), 2024)
Single mothers have experienced increasing work requirements both in the UK and in other developed countries. Little is known how increasing working hours may have affected their mental health. We investigate the impact of increasing working hours on mental health of single mothers, and compare this relationship to that for partnered mothers. We used 13 waves of the UKHLS (2009-2023) to estimate the relationship between changing working hour categories (1-16 hour per week vs. 17-25; 26-35; 36-40; and 41+) and mental health using fixed-effects models. We also investigated the role of potential mechanisms linking higher working hours and mental health, including role strain and additional income. Our findings suggest that increasing working hours from low (1-16 hours per week) to higher categories has a negative and progressively worsening relationship with the mental health of single mothers. Increasing hours to 17-25, 26-35, 36-40, and 41+ is associated with lower GHQ-12 scores by -0.7, -0.5, -0.8, and -1.1 respectively. For partnered mothers, there is no significant relationship with mental health across any of the higher working hour categories. Further analyses suggest increased role strain for single mothers as a mechanism helping explain these differences. We have found that higher working hours relative to part-time may be contributing to the worsening mental health of single mothers, at least in part due to increased role strain of having to balance work and family responsibilities. Such effects should be considered when developing future welfare policies for single mothers, to ensure that greater work requirements do not undermine the mental health of the already vulnerable population group.
Keywords: J13; J16; J22; 330; mental health; working hours; single mothers; partnered mothers; inequalities